Description of two new species of the genus Pteromalus Swederus (Hymenoptera, Pteromalidae, Pteromalinae) from Xinjiang, China - Qin Li; Ya-Lin Liu; Guo-Hua Yan; Tong-You Zhang; Hui Xiao; Hong-ying Hu (ZooKeys)
Two new species of Pteromalus Swederus (Hymenoptera, Pteromalidae, Pteromalinae), Pteromalus steppensis Li & Hu, sp. nov. and Pteromalus xiaomoheensis Yan & Li, sp. nov., are described and illustrated for the first time. Pteromalus steppensis Li & Hu, sp. nov. was reared as a primary, solitary ectoparasitoid of the larval and pupal stages of Orchestes steppensis Korotyaev, 2016 (Coleoptera, Curculionidae). Figures of its development and its host damage are also provided.